2017
DOI: 10.1136/jmedgenet-2017-104837
|View full text |Cite
|
Sign up to set email alerts
|

Their loss is our gain: regressive evolution in vertebrates provides genomic models for uncovering human disease loci

Abstract: Throughout Earth's history, evolution's numerous natural 'experiments' have resulted in a diverse range of phenotypes. Though de novo phenotypes receive widespread attention, degeneration of traits inherited from an ancestor is a very common, yet frequently neglected, evolutionary path. The latter phenomenon, known as regressive evolution, often results in vertebrates with phenotypes that mimic inherited disease states in humans. Regressive evolution of anatomical and/or physiological traits is typically accom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 77 publications
1
24
0
Order By: Relevance
“…In this work, we devised a novel approach to automate the survey of genomes for instances of coding gene sequence erosion. Knowledge of gene losses has far-reaching applications in studying the morphological and physiological adaptations of different species [10], in discovering alternative molecular pathways for critical genes [2], in medical genetics [13], and even in animal conservation programs [12]. We designed our approach for low false positive rates in order to be practically useful for the experimentalists tackling these research efforts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, we devised a novel approach to automate the survey of genomes for instances of coding gene sequence erosion. Knowledge of gene losses has far-reaching applications in studying the morphological and physiological adaptations of different species [10], in discovering alternative molecular pathways for critical genes [2], in medical genetics [13], and even in animal conservation programs [12]. We designed our approach for low false positive rates in order to be practically useful for the experimentalists tackling these research efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Species with hiconfErosion that tolerate functional changes known to cause disease in humans provide intriguing potential for medical genetics [13]. Some of these "knockout experiments of nature" may tolerate and even derive selective advantage from gene loss(es) because of factors specific to their habitat niche.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies that investigated the genomes of subterranean mammals showed that many genes involved in eye development and function are diverged or lost in these species (9)(10)(11)(12)(13)(14). Naturallyoccurring or laboratory-induced gene-inactivating mutations in some of these genes in humans or mice cause malformation of eye structures and impaired vision (15)(16)(17)(18)(19), suggesting that the gene losses observed in subterranean mammals contributed to the evolution of degenerated eyes.…”
Section: Introductionmentioning
confidence: 99%
“…Whole genome sequencing has greatly expanded our capacity to comprehend evolutionary history, the role of adaptation or the basis for phenotype differences across the tree of life. Multigenome comparisons have also been powerful to recognize the molecular basis of human diseases, a field named as phylomedicine [1821]. Here we investigate the evolution of DRD 5 in mammalian species.…”
Section: Introductionmentioning
confidence: 99%